In-field collection and preservation of decomposing human tissues to facilitate rapid purification and STR typing. (September 2018) - Holmes, Amy S.; Roman, Madeline G.; Hughes-Stamm, Sheree
Highlights: Tissues were stored in modified TENT preservative or FTA Elute Cards up to 6 months. Tissues stored in TENT had higher DNA quantities and more complete STR profiles. PDQeX DNA extraction provided the most complete STR profiles in under 20 min. DNA suspended in TENT facilitated fast purification or direct PCR for fresh tissues. Abstract: Short tandem repeats (STR) are currently the gold standard in human identification for forensic casework purposes, and successful STR typing is dependent on sufficient quantity and quality DNA. In the aftermath of a mass disaster and some forensic cases, human remains are recovered for identification in various stages of decomposition, and ideally these remains are transported to a refrigerated facility in order to halt the decomposition process and preserve the integrity of DNA within the tissue. However, in situations where refrigeration is not available (e.g., after a mass disaster or in rural forensic casework), remains continue to be exposed to environmental insults after collection, causing further DNA damage and degradation. Therefore, successful STR typing is dependent on the time of collection and preservation of the DNA sample. This study aims to test two simple in-field collection and preservation methods for decomposing human tissues that are subsequently stored at room temperature for up to six months either in a tissue preservative solution (modified TENT buffer) or on an FTA ® Elute Card. In addition, these collection and preservation methods were tested for their ability to facilitate more direct and faster processing of DNA from preserved tissues or DNA leached into the surrounding TENT preservative solution for STR typing. Pre-PCR methods tested in this study include a quick lysis of FTA ® Elute Cards, silica-based purification (QIAquick ® ), enzyme-based extractions (PDQeX), and simple dilution of liquid preservative. The traditional DNA analysis pipeline, which includes DNA extraction and quantification, will be compared to an alternate direct PCR method, thereby allowing the elimination of these two time-consuming and costly steps. The results indicate that modified TENT preservative and FTA ® Elute Cards both preserved DNA from relatively fresh tissue for up to six months at room temperature. However, mostly partial profiles were produced from decomposed tissues (day 6 – day 14 in this study) when stored for up to six months compared to when tissues were processed immediately following collection. Overall, the modified TENT preservative produced higher DNA concentrations and more successful STR results than FTA ® Elute Cards. In addition, a rapid DNA extraction platform (PDQeX) generated the most successful STR typing results from the decomposed tissues stored in TENT for up to six months at room temperature. The direct PCR method used in this study generated comparable STR results to the traditional DNA analysis approach, warranting further investigation of direct PCR methods for forensic casework type samples.